Critical review of the role and mission of TAPI on technology transfer and commercialization - Javate, Romeo M.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2012)
As we move further into the 21th century, increasing emphasis is being given on the importance of technology transfer. Through new research and practices, scholars, practitioners and policymakers have made great strides in broadening our understanding and ability to implement technology transfer and commercialization process. (John Sibley Butler and David V. Gibson). Technology transfer is a dynamic area of study that examines traditional topics such as intellectual property management, the management of risk, market identification, the role of public and private labs, and the role of universities. However, Commercialization is the process of transforming new technologies into commercially successful products. The commercialization process includes such efforts as market assessment, product design, manufacturing engineering, management of intellectual property rights, marketing strategy development, raising capital and worker training. Typically, commercialization is a costly, lengthy process with a highly uncertain outcome. The Technology Application and Promotion Institute (TAPI) is mandated to serve as the implementing arm of the Department of Science and Technology (DOST) in promoting the commercialization of technologies and in marketing the services of the other operating units. The study was focused on the technology transfer and commercialization assistance program of the Institute that identified and eliminated some barriers and obstacles to improve the implementation of TAPI's technology transfer and commercialization specifically on Venture Financing, Piloting and Prototyping Programs. The study recommended that TAPI adapts some of the good practices/systems from other countries conducive to the Institute's role and mission. Empirical evidence suggests that the Philippines not only under perform on innovation inputs such as R&D expenditures, but also experience inefficiencies in the way innovation resources are utilized within the national innovation system. The study highlighted some success factors of the enterprises and university assisted under the technology transfer and commercialization program of the Institute and eliminated the factors that brought about the failure of the project. One of the success factors considered as the best indicator of success is the transformation of a technology-based enterprise from a small to a medium enterprise like the case of Juboken Enterprises and Sunlight Foods Corporation. It also features the technology communication system of the United States of America (USA) where the government initiated exclusive technology transfer organization focusing on information distribution, and the evaluation of individual technology are conducted by the private sector, research centers, and individual technology transfer centers within the universities. Like the strategy applied by the Korea Technology Transfer Center (KTTC) which focused on technology commercialization oriented policy and systems to determine the results with the utilization in industry, it includes integrating business and technology with competitive advantages in areas like, technology transfer, valuation and investment. KTTC also created a technology platform where new technologies are turned into new business opportunities by means of technology incubation and its proper transfer. These identified systems are strongly recommended to be adapted in the technology transfer and commercialization system of the Department. The study also featured a recommendation that TAPI should further enhance collaboration with SUCs, government and non-government institutions' research and development centers, Science and Technology Parks and Technology Business Incubators. The collaboration will create precise linkages regarding the technologies for research which have potential commerciability and focus on market-driven technologies for industry utilization. The proposed tie-up program between TAPI and the Technology Resource Center (TRC) is strongly recommended by which TRC's Guarantee Fund Program can complement the Venture Financing program of TAPI that will accelerate the initial commercialization of new technologies developed by the S&T community by providing support to MSMEs, technology-based enterprises (scale-up stages) and to the creation of new and spin-off companies. TRC will guarantee the financial assistance to be provided by TAPI to the enterprise in case the latter fails to refund the financial assistance. TAPI can assist the locators in the open TBI project of TRC by providing the initial funding requirement for the initial/trial production of their products prior to full commercialization and become technology-based enterprises or spin-off companies. Based on the findings of the study, the technology transfer and commercialization program of TAPI (venture, piloting and prototyping) is a very good/helpful program and will greatly contribute to boost the economy of the country. It will also increase the opportunity of the country's export market and stay in the competition. TAPI should pursue the implementation of the program considering its huge and significant impact to the improvement of the capabilities and operations of the SMEs, technology-based enterprises and to the creation of new and spin-off companies. The study also featured a recommendation that TAPI should consider implementing one of its core function under Executive Order No. 128 which to undertake contract research particularly at the pilot plant and semi commercial stage of technologies prior to full commercialization. This is important to ensure that the technologies being transferred are fully developed and ready for commercialization and create more start-up business.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Technology Application and Promotion Institute (Philippines) .; Technology transfer -- Philippines